2022
DOI: 10.3390/pharmaceutics14051095
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release Nanosystems with a Dual Function of Targeted Therapy and Radiotherapy in Colorectal Cancer

Abstract: Nanoparticles are excellent platforms for several biomedical applications, including cancer treatment. They can incorporate different molecules to produce combinations of chemotherapeutic agents, radionuclides, and targeting molecules to improve the therapeutic strategies against cancer. These specific nanosystems are designed to have minimal side effects on healthy cells and better treatment efficacy against cancer cells when compared to chemotherapeutics, external irradiation, or targeted radiotherapy alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…In in vitro drug release experiments, we proved that the release of PFD gradually increased with the extension of time and remained stable after 36 hours, confirming the good biological stability of PFD, which laid a solid foundation for its long-term circulation and sustained release in vivo [ 45 ]. The results of CCK-8, colony formation, and apoptosis confirmed the killing effect of PPL NPs on LX2 cells; we found that PPL NP treatment alone had the least toxicity to LX2 cells, while combined with LIFU, cytotoxicity and apoptosis were at the same concentration.…”
Section: Discussionmentioning
confidence: 95%
“…In in vitro drug release experiments, we proved that the release of PFD gradually increased with the extension of time and remained stable after 36 hours, confirming the good biological stability of PFD, which laid a solid foundation for its long-term circulation and sustained release in vivo [ 45 ]. The results of CCK-8, colony formation, and apoptosis confirmed the killing effect of PPL NPs on LX2 cells; we found that PPL NP treatment alone had the least toxicity to LX2 cells, while combined with LIFU, cytotoxicity and apoptosis were at the same concentration.…”
Section: Discussionmentioning
confidence: 95%
“…There have been two recent reviews of radiolabelling approaches for nanoparticles, though these are not albumin-based [ 37 , 38 ].…”
Section: Design Challengesmentioning
confidence: 99%
“…Colorectal cancer (CRC) is ranked as the third most prevalent disease globally and one of the most destructive forms of cancer [ 2 ]. Several factors, including genetics, lifestyle, diet, and the immune system, are related to colon cancer etiology.…”
Section: Introductionmentioning
confidence: 99%
“…CRC affects the lining of epithelial cells in the colon’s lumen, and the degree of invasion, lymph node metastasis, and distant metastasis characterize its progression. Consequently, CRC management is greatly influenced by the tumor’s characteristics and the patient’s response [ 2 ].…”
Section: Introductionmentioning
confidence: 99%